"…It's Just Very Hard To Fail A Student…": Decision-Making And Defences Against Anxiety – An Ethnographic And Practice-Near Study Of Practice Assessment Panels. Issue 1 (2nd January 2017) - Finch, Jo
Abstract : The practice learning site is an important place of determining suitability for social work practice and as such is a key site of gate keeping. Research, both international and multi-disciplinary have consistently highlighted the challenging emotional processes involved in failing a student in a practice learning setting. This research has largely focused on practice educators. What has been not been explored however, are wider decision-making processes about students who have failed the placement, namely, what is known in the UK as the Practice Assessment Panel (PAP). The paper thus documents findings from an ethnographic study of four PAPs in England, utilising a practice-near analytical approach. Findings centre around three key themes; the deferring of difficult decisions, powerful voices and the unacknowledged emotional climate. The paper concludes that the PAP can be theorised as a powerful projective field and suggests possible ways forward in light of the themes to emerge.